Radio abstracts and references (Proceedings of the Institute of Radio Engineers, 1933)
This is prepared monthly by the US Bureau of Standards, and is intended to cover the more important papers of interest to the professional radio engineer which have recently appeared in periodicals, books, etc. The number at the left of each reference classifies the reference by subject, in accordance with the "Classification of Radio Subjects: An Extension of the Dewey Decimal System," Bureau of Standards Circular No. 385, which appeared in full on pp. 1433-56 of the August, 1930, issue of the PROCEEDINGS of the Institute of Radio Engineers. The articles listed are not obtainable from the Government or the Institute of Radio Engineers, except when publications thereof. The various periodicals can be secured from their publishers and can be consulted at large public libraries.